2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path787>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gastrointestinal morphology associated with obstructive jaundice

Abstract: Bacterial translocation has been consistently demonstrated in experimental models of obstructive jaundice. An important factor which promotes this phenomenon is physical injury of the intestinal mucosa. Some previous studies have presented suggestive evidence of this, following bile duct ligation. The aims of this study were to analyse objectively intestinal mucosal morphometric characteristics, to examine for evidence of bacterial translocation, and to assess enterocytes for ultrastructural abnormalities. Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 25 publications
(40 reference statements)
2
33
1
5
Order By: Relevance
“…Although some authors suggest that the presence of bile or (nonconjugated) bile salts, per se, avoids transmigration of endotoxins through the epithelium (4,40,41), others believe that the filter function of Kupffer cells is the crucial factor in the prevention of systemic endotoxemia (13). However, in the current study, a significant reduction of both the permeability of endotoxin through IEC and the production of proinflammatory cytokines by leukocytes after addition of bile and its components became evident.…”
mentioning
confidence: 99%
“…Although some authors suggest that the presence of bile or (nonconjugated) bile salts, per se, avoids transmigration of endotoxins through the epithelium (4,40,41), others believe that the filter function of Kupffer cells is the crucial factor in the prevention of systemic endotoxemia (13). However, in the current study, a significant reduction of both the permeability of endotoxin through IEC and the production of proinflammatory cytokines by leukocytes after addition of bile and its components became evident.…”
mentioning
confidence: 99%
“…The studies made for determining if the physical damage in the intestinal mucosa causes the translocation of endogenous bacteria show that, the physical damages resulting with the elimination of the obstacles between the intestine lumen and lamina propria causes the translocation of bacteria thorough the gastrointestinal tract [6]. As the result of the studies, bacterial translocation was observed 7 days after the obstructive jaundice on rats [4,7,8]. Again, the hypothesis that the intestinal damage in rats having jaundice mainly occurs at terminal ileum, were justified with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the BT in bile duct ligated models was investigated before (15)(16)(17)(18)(19)(20)(21)(22), in many of them (15)(16)(17)(19)(20)(21)(22)) the effects of different materials on BT, except food with high-fa was studiedt. In previous studies, the effects of high-fat enteral nutrition on BT were studied by Luyer et al (10,11,18).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, some studies which investigate the BT in obstructive jaundice models have been carried out (15)(16)(17)(18)(19)(20)(21)(22). In some of them, different materials were given to the models in whom bile duct was ligated to observe their effects on BT (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%